Pengaruh Keberwujudan,Keandalan,Ketanggapan,Jaminan Dan Kepedulian Terhadap Kepuasan Dan Loyalitas Orang Tua Pada MI Negeri Grogol - Mulyanto, Mulyanto; Nasirin, Irsam (-)
The purpose of this study was to examine the effect of tangible, realiability,responsiveness,assurance and care for a parent satisfaction and loyalty to the MI State Grogol Sukoharjo district. The technique of determening the sample in this study with census method that sampled all members of the population, as many as 100 parents of students, data analysis using path analysis (Path Analysis).Keywords: tangible,reliability,resposiveness,assurance,care,loyalty